HCI at the end of life: understanding death, dying, and the digital - Massimi, Michael; Odom, Will; Kirk, David; Banks, Richard (Proc. CHI 2010 Extended Abstracts, 2010)
Death and our experience of it is a fundamental aspect of life and consequently every human culture has developed practices associated with responding to, signifying, and dealing with its implications. As our technology pervades our cultures, we find that the digital is increasingly intersecting with these practices. This raises issues which have rarely been conceptualized or articulated in the HCI and CSCW communities. It is increasingly important to design "thanatosensitive" technologies which support death-centric practices such as collaborative acts of remembrance, bequeathing of digital data, or group reflection on the digital residua of a life. This workshop will bring together participants interested in such technologies and their implications. Potential topics include, but are not limited to: devices for reflection and meaning-making across multiple lifespans; interdisciplinary practices surrounding mortality, dying, and death; technology heirlooms; digital rights management; and methodological approaches to researching end-of-life technology issues.